The Difference of Anxiety between Primigravide Normal Pregnancy and Severe Preeclamsia at Dr. Moewardi Hospital - Sani, Azizah Amalia Novia; Anggraini, Nutria Widya Purna; Wicaksono, Bagus (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2015)
Background: Women with first ongoing pregnancy (primigravide) came through physical and physicological adaptation which can lead into physicological problem. High-risk pregnancy like preeclamsia have some complication thatÂ increased women worries which causing anxiety in their pregnancy. Mental burden in high-risk pregnancy causing some problem toward both motherâs and fetusâs health quality and also complication in labor. This study aimed to know difference of anxiety between primigravide normal pregnancy and severe preeclamsia. Methods: This study was an analitycal observasional study with cross sectional approach taken at Obstetri and Gynecologi Policlinic ofÂ Dr. Moewardi Hospital, in Desember 2014 until January 2015. The sampling method was using purposive sampling. There were 40 respoden in total which devided into 20 responden of normal pregnancy and 20 responden of severe preeclamsia. Anxiety level was measured using HARS (Hamilton Anxiety Rating Scale) questionnaire. Data was analyzed using Chi square test to compare anxiety differences between the two group. Results: It was found 8 participant (40%) show no anxiety and 12 participant (60%) having mild anxiety in normal pregnancy. While in severe preeclamsia was found 5 participants (25%) having mild anxiety, 13 participants (65%) having moderate anxiety, and 2 participant (10%) having severe anxiety. The result of analysis by Fischer exact test showed p=0,002 (p<0,05). Conclusions: There was an anxiety difference between primigravide normal pregnancy and severe preeclamsia Keywords: anxiety, pregnancy, preeclamsiaÂ